2021
DOI: 10.15326/jcopdf.2020.0140
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Emphysema and Small Airways Disease in Cigarette Smokers

Abstract: For personal use only. Permission required for all other uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…CT scans could detect emphysema in patients who do not meet the spirometry standards of COPD in 20% of smokers. 2 , 32 Lung function combined with chest CT may be better for assessing the disease progression and identifying subjects at risk of progression. In our study, the correlation analysis revealed that CD19 and POU2AF1 were significantly associated with lung function and CT indexes of emphysema.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CT scans could detect emphysema in patients who do not meet the spirometry standards of COPD in 20% of smokers. 2 , 32 Lung function combined with chest CT may be better for assessing the disease progression and identifying subjects at risk of progression. In our study, the correlation analysis revealed that CD19 and POU2AF1 were significantly associated with lung function and CT indexes of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…1 As an important pathological manifestation of COPD, emphysema is defined as “abnormal permanent enlargement of air spaces distal to terminal bronchioles, accompanied by destruction of their walls without obvious fibrosis”. 2 Emphysema has been recognized as one of the COPD phenotypes and may be present in other phenotypes, as well as in smokers without COPD. 3 Moreover, emphysema is associated with the severity and progression of COPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 This PRM approach was also successfully used in smokers without COPD, where it showed that these metrics can identify unique patterns of progression, and that both PRM fSAD and PRM EMPH , ie, PRM-derived emphysema, can independently predict future development of emphysema. 59 , 60 Bronchiectasis was also found to be associated with increased emphysema in smokers and those with both bronchiectasis and emphysema had lower FEV 1 and 6MWD. 17 In current or former smokers, the low attenuation area on low-dose CT imaging ordered as part of routine lung cancer screening may be able to detect quantitative emphysema and diagnose subjects with early COPD, allowing clinicians to monitor patients closely and perhaps initiate appropriate treatment when needed.…”
Section: Commercial Platformsmentioning
confidence: 96%
“…Studies have shown that the small airways contribute significantly to airflow obstruction in both COPD [ 4 ] and asthma [ 5 ]. Characterised by inflammation, hypersecretion of mucus and airway remodelling [ 6 ], small airways obstruction (SAO) has been shown to precede both emphysematous changes and reduction in traditional spirometric parameters in COPD [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%